Pemberian Edukasi William Flexi Exercise untuk Low Back Pain Myogenic pada Lansia di Desa Nguter - Luluk Setya Arimbi; Farid Rahman; Sartini Sartini (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Nguter is one of the villages in Nguter Subdistrict, Sukoharjo Regency, Central Java. The geographical location of Nguter Subdistrict is at an altitude of 104 meters above sea level. One of the healthcare facilities in Nguter Village is the Nguter Community Health Center (Puskesmas). From January to July 2024, the number of low back pain cases treated at Nguter Community Health Center reached 285 people. This figure is considered quite hi gh, as it continues to show a significant increase each year. The goal of this program is to provide education on William Flexi Exercise for myogenic low back pain in the elderly, helping alleviate the complaints of lower back pain. The method used involves counseling sessions through lectures and leaflets for the Elderly Posyandu Community in RW 07, Nguter Subdistrict, Sukoharjo Regency, Central Java. The result of this community service program is that the elderly understood the material provided and are able to perform the exercises independently at home.